The Cambridge companion to Jewish theology - Kepnes, Steven (Cambridge companions to religion, 2020)
"Introduction to The Cambridge Companion to Jewish Theology Steven Kepnes The reader will find here, in this Cambridge Companion to Jewish Theology, essays by leading Jewish Studies scholars that display the Jewish theological tradition as long, sustained, complex, and deep. This collection aims to show this with essays that cover the full historical span of Judaism from the Biblical through to the contemporary periods. Each essay is a gem filled with not only an overview of a topic that employs and reviews the best in contemporary scholarship, but also brings important new insights to it. One thing that will become obvious for the reader is the variety of theological approaches that Jews have taken to presenting and understanding God. For example, on the crucial issue of revelation, Alan Brill presents us with seven models of revelation in modern Jewish theology. I should also say, from the outset, that Jewish theology encompasses not only the issue of the nature of God but also the dynamic of inter-relations between God and humans and God and the world. I have attempted to focus the attention of my authors mainly on God but, quite naturally, a number of authors also discuss the relations between God and humans, God and the world. Here, for example, a figure like Emmanuel Levinas stands out for wanting to focus almost exclusively on ethical relations between humans"--